Biodegradable polymer–platinum drug conjugates to overcome platinum drug resistance. Issue 101 (1st October 2015) - Yang, Qiang; Qi, Ruogu; Cai, Jing; Kang, Xiang; Sun, Si; Xiao, Haihua; Jing, Xiabin; Li, Wenliang; Wang, Zehua
Abstract : Biodegradable polymers with pendent pair-wised carboxylic acids but lacking sulfur were used to chelate oxaliplatin prodrug which self-assembled into micelles in water for drug delivery. Abstract : Drug resistance and severe dose-dependent side effects are the major obstacles to the further use of platinum agents. Two well-acknowledged mechanisms of resistance are the decreased intracellular accumulation and the increased sulfur-binding-detoxification of platinum agents. The polymer–drug conjugate approach can remarkably enhance the uptake of substances by cancer cells, therefore can achieve better anticancer effects with lower dosage, and thus reduce the dose-dependent side effects. Here we synthesized a biodegradable polymer containing pendant 1, 2-bidentate carboxyl groups to chelate platinum without introducing sulfur atoms to potentially detoxify the platinum drugs. The polymer–platinum conjugate formed nanomicelles showed significantly increased intracellular accumulation and could partially overcome drug resistance in ovarian cancer cells.